Monitoring pollution of coastal lagoon using Liza aurata kidney oxidative stress and genetic endpoints: an integrated biomarker approach - Oliveira, M.
Despite the importance of fish kidney in several functions (immune, metabolism and excretion of xenobiotics) its use in coastal water biomonitoring focusing on protection and damage is scarce. Five critical sites in Ria de Aveiro (Portugal; Barra—BAR, Gafanha—GAF, Rio Novo do Principe—RIO; Laranjo—LAR and Vagos— VAG) were assessed in comparison to a reference site (Torreira—TOR), focusing on Liza aurata kidney antioxidant defences versus damage responses. Non protein thiols were higher at RIO (near a former bleached kraft pulp mill effluent) and total glutathione at RIO, LAR (mercury contaminated) and VAG (polycyclic aromatic hydrocarbons contaminated). Catalase and glutathione S-transferase activities were higher at RIO and LAR whereas no differences were found in glutathione peroxidase activity. However, glutathione reductase was higher at BAR (subject to naval traffic), GAF (harbour water area), RIO and LAR. No peroxidative damage was observed despite the decreased DNA integrity at RIO and VAG. The integrated biomarker response index ranked impacted sites as: LAR>RIO>BAR>GAF>VAG>TOR.